Oxidation inhibited graphite enhances Lamons' gaskets. Issue 9 (September 2016) - Unknown
Abstract : Lamons, a major US-based supplier of gaskets and bolts, has announced that all of its standard spiral wound gaskets (SWGs), corrugated metal gaskets, Kammprofile and Corrukamm gaskets that are graphite faced will be manufactured with its new O2i oxidation inhibited graphite.